Retrotransposon accumulation and satellite amplification mediated by segmental duplication facilitate centromere expansion in rice - Ma, Jianxin; Jackson, Scott A. (Genome Research, 2006)
The abundance of repetitive DNA varies greatly across centromeres within an individual or between different organisms. To shed light on the molecular mechanisms of centromere repeat proliferation, we performed structural analysis of LTR-retrotransposons, mostly centromere retrotransposons of rice (CRRs), and phylogenetic analysis of CentO satellite repeats harbored in the core region of the rice chromosome 4 centromere (CEN4). The data obtained demonstrate that the CRRs in the centromeric region we investigated have been enriched more significantly by recent rounds of segmental duplication than by original integration of active elements, suggesting that segmental duplication is an important process for CRR accumulation in the centromeric region. Our results also indicate that segmental duplication of large arrays of satellite repeats is primarily responsible for the amplification of satellite repeats, contributing to rapid reshuffling of CentO satellites. Intercentromere satellite homogenization was revealed by genome-wide comparison of CentO satellite monomers. However, a 10-bp duplication present in nearly half of the CEN4 monomers was found to be completely absent in rice centromere 8 (CEN8), suggesting that CEN4 and CEN8 may represent two different stages in the evolution of rice centromeres. These observations, obtained from the only complex eukaryotic centromeres to have been completely sequenced thus far, depict the evolutionary dynamics of rice centromeres with respect to the nature, timing, and process of centromeric repeat amplification.